Selección de los animales en base a los caracteres de importancia económica en la producción de leche con el objetivo de mejora genética en la parroquia Toacaso. - Villacis Bustamante, Jhoselym Victoria (2023)
Genetic improvement in dairy cattle has two approaches, production and efficient reproduction. The small and medium-size producers of the Toacaso parish manage non-technified productions with a traditional-family breeding, in the genetic improvement program the reproductive techniques propose to improve the productive levels from AI with heat detection and IATF with cows that present energetic and hormonal imbalances, anestrus or nutritional alterations. Therefore, referring to the reproductive part, the factors affecting cow fertility are related to body condition, energy balance, nutrition, calving interval and days of lactation. So, within production, milk composition is regulated by several factors, one of the most important of which is genetics. The research was conducted with 21 producers who linked 94 cattle to the genetic improvement project. Also, periodic visits were made every weekend, where data updating, animal weighing, deworming, vitaminization, milk quality control, gynecological controls and artificial insemination were carried out. Based on the production needs in the parish, three variables were selected; fertility, daily weight gain and milk quality. In the fertility analysis, 30 cows were found to be empty for a prolonged period of time, calculating that the lost is $15240, while the average daily weight gain is 471,41 g/day and it is estimated to reach 650 g/day. And in the parish, there is an average production of 9 to 12 liters/day per cow, the milk density is 29,02 (1,029 g/ml) and the incidence of mastitis is low within the productions. Finally, in reference to the variables evaluated, 3 cows with good reproductive and feeding efficiency were selected to be the future mothers of the breeders and to be able to disseminate their genetics in the productions.